A tungsten polyoxometalate mediated aqueous redox flow battery with high open-circuit voltage up to 2 V - Weipeng Li; Weizhuo Xu; Zhaopeng Sun; Linning Tang; Guohao Xu; Xinyue He; Yulin Deng; Wei Sun; Bingjie Zhou; Jianfei Song; Wei Liu (Nature Communications)
Abstract As a promising stationary energy storage device, aqueous redox flow battery (ARFB) still faces the challenge of low open-circuit voltage, due to the limitation of the potential of water splitting (1.23 V theoretically). Herein, we present a low potential anolyte design by using Na substituted phosphotungstic acid (3Na-PW12) for an aqueous redox flow battery with the high open-circuit voltage up to 2.0 V. The 3Na-PW12 can store 5 electrons in the charging process and simultaneously capture Na+ or protons from the dissociation of water, resulting in the increase of electrolyte pH to 11. Because of the high pH value, the hydrogen evolution reaction (HER) is highly suppressed, and the 3Na-PW12 is partially degraded into a lacunary structured PW11 with extremely low potential down to −1.1 V (vs. SHE). After discharging, the captured protons are re-released into the solution, therefore, pH and the structure of 3Na-PW12 are recovered. Based on the cyclic pH change and self-regulation process of 3Na-PW12 in the charge and discharge process, the aqueous flow battery offered a high-power density of 200 mW cm−2 and 160 mW cm−2 coupled with Br2/Br− and I2/I− catholyte respectively.